Children cry alone - Marium, Lubna; Child Development Centre (Bangladesh); INCIDIN (Organization) (Dhaka : Ain o Salish Kendra, 2004)
With reference to Bangladesh.
Includes bibliographical references.
BIED
Complimentary copy from BIED
Keywords: Child sexual abuse -- Bangladesh; Sexually abused children -- Bangladesh; Child welfare -- Bangladesh; Social advocacy -- Bangladesh